Anti‐neuroinflammatory effect of daidzein in human hypothalamic GnRH neurons in an in vitro membrane‐based model. (21st December 2020) - Morelli, Sabrina; Piscioneri, Antonella; Guarnieri, Giulia; Morelli, Annamaria; Drioli, Enrico; De Bartolo, Loredana
Abstract: Phytoestrogens can control high‐fat diet‐induced hypothalamic inflammation that is associated with severe consequences, including obesity, type 2 diabetes, cardiovascular and neurodegenerative diseases. However, the phytoestrogen anti‐neuroinflammatory action is poorly understood. In this study, we explored the neuroprotection mediated by daidzein in hypothalamic neurons by using a membrane‐based model of obesity‐related neuroinflammation. To test the daidzein therapeutic potential a biohybrid membrane system, consisting of hfHypo GnRH‐neurons in culture on PLGA membranes, was set up. It served as reliable in vitro tool capable to recapitulate the in vivo structure and function of GnRH hypothalamic tissue. Our findings highlighted the neuroprotective role of daidzein, being able to counteract the palmitate induced neuroinflammation. Daidzein protected hfHypo GnRH cells by downregulating cell death, proinflammatory processes, oxidative stress, and apoptosis. It also restored the proper cell morphology and functionality through a mechanism which probably involves the activation of ERβ and GPR30 receptors along with the expression of GnRH peptide and KISS1R.